120 Factors associated with extended survival for patients with platinum-resistant ovarian cancer (PROC) treated with modified vaccinia oncolytic virotherapy (VOV). (18th September 2019) - Manyam, M; Stephens, A; Kennard, J; Fitzsimmons, C; Kendrick, J; McKenzie, N; LeBlanc, J; Smith, J; Ahmad, S; Holloway, R
Abstract : Objectives: VIRO-15 phase IB trial (NCT02759588 ) enrolled 11 patients with PROC, extensive tumor burden, and median 5 prior lines of therapy. We aimed to retrospectively determine factors that predict clinical benefit from VOV monotherapy in PROC. Methods: Patients received a modified VOV (GL-ONC1, Genelux Corp.) intra-peritoneally on two consecutive days. Four patients had apparent clinical benefit with >5 mos progression-free survival (PFS) following virotherapy (A). Seven (B) patients had <5 mo PFS. Comparative analyses included: measures of immune-competence with neutralizing antibody (NA) titers, virus-encoded glucuronidase activity (GA), tumor response by RECIST 1.1, Prognostic Nutritional Index (PNI), circulating tumor cells (CTCs), number of prior platinum and total therapies. Mann-Whitney test, t- test, z- test were used to evaluate differences between the groups. Results: Following GL-ONC1, the PFS was 10.9±5.1 and 2.4±1.1 mos for A vs B ( p < 0.05). Mean OS for A was 21.7±8.2 mos vs 3.6±1.5 mos for B ( p <0.05). Three A pts are alive, and one with stable disease died at 8-mos from pulmonary embolism. Factors that predicted clinical benefit were: i) PNI [mean 49.0±5.7 vs 42.1±4.3 ( p <0.05)], ii) Week-5 CA125 values < Week-2 [4/4 vs 0/7 ( p <0.01)], iii) absence of CTC [3/4 vs 1/7 pts ( p <0.05)]. Conclusions: Factors associated with clinical benefit post GL-ONC1 monotherapy in PROC include higher PNI, absence of CTCs, and Week-5 CA125 less than Week-2 levels. In the absence of these factors, cytotoxic therapy should be considered by Week-6 following GL-ONC1. Three patients are currently alive at 22.8–28.2 mos, following additional therapies.